2020
DOI: 10.1142/s021949882250013x
|View full text |Cite
|
Sign up to set email alerts
|

Rings with fine idempotents

Abstract: An idempotent in a ring is called fine (see G. Călugăreanu and T. Y. Lam, Fine rings: A new class of simple rings, J. Algebra Appl. 15(9) (2016) 18) if it is a sum of a nilpotent and a unit. A ring is called an idempotent-fine ring (briefly, an [Formula: see text] ring) if all its nonzero idempotents are fine. In this paper, the properties of [Formula: see text] rings are studied. A notable result is proved: The diagonal idempotents [Formula: see text] ([Formula: see text]) are fine in the matrix ring [Formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Lam decomposition have high indices of nilpotence because they correspond to the strictly upper part of a matrix in good form. The rings whose nonzero idempotents are fine turned out to be an interesting class of indecomposable rings and were studied in [2] by Cǎlugǎreanu and Zhou. In 2021, the same authors focused on rings in which every nonzero nilpotent element is fine, which they called N F rings, and showed that for a commutative ring R and n ≥ 2, the matrix ring M n (R) is N F if and only if R is a field; see [3].…”
Section: Introductionmentioning
confidence: 99%
“…Lam decomposition have high indices of nilpotence because they correspond to the strictly upper part of a matrix in good form. The rings whose nonzero idempotents are fine turned out to be an interesting class of indecomposable rings and were studied in [2] by Cǎlugǎreanu and Zhou. In 2021, the same authors focused on rings in which every nonzero nilpotent element is fine, which they called N F rings, and showed that for a commutative ring R and n ≥ 2, the matrix ring M n (R) is N F if and only if R is a field; see [3].…”
Section: Introductionmentioning
confidence: 99%
“…The rings whose nonzero idempotents are fine turned out to be an interesting class of indecomposable rings and were studied in [2] by Cǎlugǎreanu and Zhou. In 2021, the same authors focused on rings in which every nonzero nilpotent element is fine, which they called N F rings, and showed that for a commutative ring R and n ≥ 2, the matrix ring M n (R) is N F if and only if R is a field; see [3].…”
mentioning
confidence: 99%
“…M 9 (F)e(2,7,4) where e (2,7,4) = e 2,2 + e 7,7 + e 8,8 + e 9,9 . Thus, N C = N 1,4,4 + N 2,7,4 satisfies N 4 C = 0 andC + N C =…”
unclassified